2021
DOI: 10.3889/oamjms.2021.6145
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Impairment in Construction Workers – Influence of Smoking and Exposure Duration

Abstract: AIM: The objective of the study was to assess the influence of exposure duration and smoking on ventilatory impairment among construction workers. METHODS: A cross-sectional study was performed, including 83 construction workers aged 18–64 years, compared to equivalent number of office controls matched by age, workplace exposure duration, and smoking status. Data on chronic respiratory symptoms, work history, and smoking status were collected by standardized questionnaire, while lung functional testing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This finding is in consistent to that of [12] In the study pulmonary functions were decreased in construction workers but the changes were restricted to small airways. [11] A total of 11 construction workers had restrictive pulmonary impairment while obstructive type of pulmonary disorder was seen in 6 construction workers. Combined type of pulmonary impairments was seen in a total of 5 construction workers.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in consistent to that of [12] In the study pulmonary functions were decreased in construction workers but the changes were restricted to small airways. [11] A total of 11 construction workers had restrictive pulmonary impairment while obstructive type of pulmonary disorder was seen in 6 construction workers. Combined type of pulmonary impairments was seen in a total of 5 construction workers.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the length of exposure to occupation-related dust among construction workers further increases their vulnerability to respiratory health problems. Recent evidence9 39 indicate that construction workers who have been in the sector for a longer period, for example, over 10 years were more likely to report respiratory health diseases than those who have spent less than 10 years as construction workers 9…”
Section: Discussionmentioning
confidence: 99%
“…Occupational health education is required as continuous conversations would increasingly improve workers’ awareness of hazards in the work sector and empower them with requisite skills and processes to protect, maintain and promote their health. In the same vein, health promotion messages through information, education and communication resources and strategies could help in preventing behavioural practices such as smoking, which could increase the vulnerability and severity of work-related respiratory diseases among construction workers 2 7 39…”
Section: Discussionmentioning
confidence: 99%
“…The types of pesticides also explained some heterogenicity with stronger and more consistent effects for organophosphate, particularly on FEV1 as compared to paraquat or non-specific pesticide exposure [46]. However, few researchers reported that aging, smoking, excessive smoking, and occupational exposure showed a significant relationship with low lung function [47][48][49]. In addition, a different pattern of lung function was found in various occupational groups exposed to pesticides.…”
Section: Relationship Between Lung Function Values and Associated Fac...mentioning
confidence: 99%